Overview of Emergency Preparedness of Nurses in Hospitals in the Face of Disasters - Zahra Ananda; Hasanatun Laili; Mayumi Ershanda; Abdurrozzaq Hasibuan (Lembaga Pengembangan Kinerja Dosen, 2024)
This research aims to identify and examine the emergency preparedness of nurses in hospitals in dealing with disasters through the literature review method. Hospitals have an important role in disaster preparedness and management, because they must be able to provide a quick and effective response to emergency situations caused by disasters. Data were collected from articles and national journals published in the last 10 years, using related keywords such as